A Novel Tongue Pressure Measurement Instrument with Wireless Mobile Application Control Function and Disposable Positioning Mouthpiece - Hsiu-Yueh Liu; Chun-Hung Chen; Chao-Hung Kuo; Ming-Chu Feng; Jen-Hao Chen; Hsuan-Wen Wang; Kun-Chun Chen; Chun-Li Lin (Diagnostics, 2021)
This study developed a novel chair-side tongue pressure (TP) measuring instrument with a disposable positioning mouthpiece controlled using a smartphone application (APP), denoted as the TP wireless application (TPWA). The mouthpiece was designed with a palate-shaped air balloon containing a tongue contact bump and a plastic bite positioning tube. Fatigue load testing was performed to evaluate mouthpiece durability by applying 700 displacement cycles (50 times a day for one week during training, with twice the safety factor) on the air balloon. The main component used in developing this instrument was a silicon pressure sensor equipped with wireless Bluetooth connection. Young (52 adults; mean age = 20.23 ± 2.17) and elderly (40 adults; mean age = 72.60 ± 7.03) individuals participated in the test with the new instrument, with the results compared to those of a commercial device. The TPWA mouthpiece fatigue test showed that mean response pressures were maintained at 12 kPa. No significant (p > 0.05) differences were found during testing repetitions 0–10 and 701–710. There were no significant differences in the maximum TP values presented between the test sequences using different instruments for young and elderly participants. The TPWA results showed that TP values gradually decreased with increasing age (40.77 kPa for young and 16.55 kPa for elderly participants). The maximum TP for males (43.51 kPa) was significantly larger than that for females (35.14 kPa) in the young group, but an opposite trend was seen in the elderly group (12.97 for males and 17.59 for females). Thus, this study developed a novel chair-side TP measurement instrument with Bluetooth wireless mobile application control. A durable positioning oral mouthpiece was approved for measuring pressure sufficiently, reliably, and precisely for TP screening.